Use of D-Squame® as a Minimally Invasive Technique to Evaluate Skin Immune Response Biomarkers in Canine Atopic Dermatitis - Marion Mosca; Nadège Milhau; Mélanie Legain; Adrien Idée; Xavier Langon; Didier Pin (Veterinary Sciences)
Evaluation of skin inflammation biomarkers in canine atopic dermatitis (AD) currently requires skin biopsies. Tape stripping has been shown to be a reliable technique to study biomarkers in the stratum corneum (SC) in humans. The aim of this study was to assess the immune response and identify biomarkers in the SC of dogs with canine AD using D-squame® as a minimally invasive technique. Eight beagle dogs were epicutaneously sensitized to Dermatophagoides farinae extract after tape stripping on sensitized site (S); twice a week for 49 days. Two sites were determined: lesional site (L) and non-lesional site (NL) on eight dogs affected spontaneously with AD. Adhesive tape strips D-Squame® were applied on each site. Skin concentrations of 10 cytokines were analyzed with an ELISA kit. Our results revealed a significant increase of IL-13, IL-4, and TNF-α concentrations in S and L sites. Regarding IFN-γ, its concentration was significantly increased in L skin and increased but not significantly in S sites. All the alarmins were not differentially expressed except IL-33 in the S site. IL-31, IL-1β, and IL-10 were not detectable. D-squame® seems to be a suitable technique to extract inflammatory cytokines from the SC of dogs, and IL-13, IL-4, TNF-α, and IFN-γ could be interesting biomarkers of canine AD.